Innovative aspects of varieties of serve in modern men's volleyball - Lutkova, N. V.; Makarov, Y. M.; Lutkov, V. F.; Dakshevich, N. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the innovative content of serve efficiency performed by highly qualified volleyball players. Methods and structure of the study. The software of the Italian company Data Project was used: Data Volley 4Pro, through the built-in functionality of which various statistical indicators of competitive activity are analyzed. Indicators of the effectiveness of serve execution were determined in various ways during the Russian Volleyball Championship among men's teams. 80 games of leading teams with the participation of 96 athletes were analyzed.